Adverse cardiac events in the treatment of non-small cell lung cancer with programmed death-1and programmed death-ligand 1 inhibitors: A protocol for systematic review and meta-analysis. Issue 32 (7th August 2020) - Li, Honglin; Han, Deting; Feng, Xiaoteng; Yu, Wenjun; Xu, Tongtong; Ma, Tao; Song, Lucheng
Abstract: Background: Programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1) inhibitors are immune therapies that have shown great promise in the treatment of multiple cancers. However, immune-related adverse events of PD-1 and PD-L1 inhibitors may limit their use in non-small cell lung cancer (NSCLC). Given the rising number of clinical trials in recent years, it is essential to perform a meta-analysis to provide assess the cardiotoxicity of PD-1/ PD-L1 inhibitors in NSCLC therapy. Method and analysis: The ClinicalTrials.gov, Embase, PubMed, and Cochrane Central Register of Controlled Trials repositories will be searched from their inception to December 2019. The bibliography of the searching process will be imported into Endnote X9 software. Two reviewers independently will screen the literature, extract data, and conduct the risk of bias for every added study. The data analysis will be analyzed using Stata15.0 software. Specific adverse cardiac events will be identified, with particular attention on atrial fibrillation, cardiac arrest, cardiac failure, and pericarditis. This review will be performed as per the Preferred Reporting Item for Systematic Review and meta-analysis statement recommendations. Ethics and dissemination: This study will provide support for the cardiotoxicity linked to the treatment of NSCLC using PD-1/PD-L1 inhibitors. The data in the meta-analysis will be retrieved from completed and published clinical trials; therefore, ethical review and patient informed consent will not be required. PROSPERO number: CRD42020156397.